Efficacy of OLIF combined with pedicle screw internal fixation for lumbar spinal stenosis on spinal canal changes before and after surgery - Wangbing Xu; Weibing Liu; Faming Zhong; Yu Peng; Xin Liu; Liangkun Yu (Journal of Orthopaedic Surgery and Research, 2023)
Abstract Purpose The purpose of the study was to evaluate the efficacy of OLIF combined with pedicle screw internal fixation in the treatment of lumbar spinal stenosis by assessing the changes in spinal canal before and after surgery. Methods In this retrospective study, we included sixteen patients who underwent a combination of single-segment OLIF and pedicle screw internal fixation for the treatment of lumbar spinal stenosis at the Affiliated Hospital of Jiangxi University of Chinese Medicine between February 2018 and August 2022. The patients' pre- and post-operative data were compared. Intraoperative bleeding, duration of surgery, visual analogue score (VAS), Oswestry Disability Index (ODI), disc height (DH), cross-sectional area of vertebral canal (CSAVC), cross-sectional area of dural sac (CSADS), cross-sectional area of intervertebral foramen (CSAIF), spinal canal volume (SCV), spinal canal volume expansion rate, lumbar lordosis, and sagittal vertical axis were observed and recorded. The efficacy of OLIF combined with pedicle screw internal fixation for lumbar spinal stenosis on spinal canal changes before and after surgery was summarized. Results The results showed that OLIF combined with pedicle screw internal fixation effectively restored disc height and increased the cross-sectional area of the spinal canal. It also had an indirect decompression effect. The intraoperative bleeding and duration of surgery were within acceptable ranges. The VAS and ODI scores significantly improved after surgery, indicating a reduction in pain and improvement in functional disability. The CSAVC, CSADS, CSAIF, SCV, and spinal canal volume expansion rate were all increased postoperatively. Additionally, there was improvement in lumbar lordosis and sagittal vertical axis. We conducted a follow-up of all patients at 1 year after the surgery. The results revealed that the parameter values at 1 year post-surgery showed varying degrees of decrease or increase compared to the immediate postoperative values. However, these values remained statistically significant when compared to the preoperative parameter values (P < 0.05). Conclusions OLIF combined with pedicle screw internal fixation effectively restores disc height and increases the cross-sectional area of the vertebral canal in patients with LSS, reflecting the indirect decompression effect. Measuring parameters such as DH, CSAVC, CSADS, CSAIF, SCV, and SCV expansion rate before and after surgery provides valuable information for evaluating the efficacy and functional recovery of the lumbar spine in LSS patients treated with OLIF surgery.